G576(P) Provision of psychological support for children & young people (cyp) with type1 diabetes: whether consistent with nice guideline and best practice tariff (bpt) criteria. (May 2019) - Gupta Dasgupta, N; Mittal, D; Javed, M
Abstract : Aim: Assess the current level of provision of psychological care to CYP with diabetes Assess if current psychology provision to CYP with diabetes meets NICE guidance and BPT criteria. Methodology: The retrospective audit has been performed from May 2015 – August 2017, from twinkle database in a span of 40 random patients. All children with abnormal PI-ED (Paediatric Index of Emotional Distress) scores has been considered. Leveraging Standardized proforma, Data has been collected about referral and assessment process. The referral pathway and outcome of referrals measured. Qualitative assessment done by assessing comments from service users. Results: 46% was actually referred to psychology service within the 100% eligible referral population. 100% of referrals were accepted. The actual appointment date from the date of referral has been observed more than 3 months most of the samples. Average length of stay with CAMHS was 6.5 months. 57% patients were overall satisfied by the service provided though only 28% felt it was 'good' while 14% were not satisfied. One among the total of 7 patients referred did not attend the appointment & self–discharged later. Feedback reflects for CAMHS service structure (e.g., choice clinics, partnership clinics etc.) lacks clarity and needs process improvement. Conclusion: Current psychology service provision to Children and young adults with diabetes reflects non-compliant result vis-à-vis with BPT standards in Walsall. Study also reflects Walsall Manor Hospital does not have any integrated psychology support within the multidisciplinary team for diabetes. Hence as a knock-on impact, it has also been seen a significant delay between day of referral and first clinic appointment provided. Future practice shall also consider active involvement of psychologists within the multidisciplinary team providing support throughout the care with a special emphasis during transition of care. It is recommended that psychologist shall be an integral part of MDT team, rather than referring patients randomly to CAMHS.